IMPLEMENTASI PAIRING SKYPE DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI DAN BERBICARA MAHASISWA SEMESTER I IKIP PGRI MADIUN - Pinandhita, Fitra; Nugroho, Andhi Dwi (IKIP PGRI MADIUN, 2014)
The aims of this research are first, to know whether or not the use of pairing skype can increase the students speaking ability. Second, to know whether or not the use of Pairing Skype can increase students motivation. Third, to know the strenghts and weaknesses of pairing skype. The subject of the research was the students of 1A of English Department of IKIP PGRI Madiun consisting of 28 students. It was a classroom action research. The researcher did some steps for each cycle. They were planning, action, observation, and reflection. In collecting the data, the researcher applied several techniques including observation, interview, questionnaire, and test. The quantitative data were analyzed by using descriptive statistics. It compared between the scores of pre test (before implementing Pairing Skype) and post test (after implementing Pairing Skype), while the qualitative data were analyzed by using constant comparative method which consist of; comparing Incidents applicable to each category, integrating categories into their properties, delimiting theory, and writing theory. The results of this research are first, the use of pairing skype can improve students speaking skill. This is indicated by some factors as follows: (1) Students are able to express ideas and content. Students focused on the purpose and the main idea of the materials; (2) Students are able to make a good organization. Students could make effective organization of the materials; (3) Students are able to use the language. Students could use correct grammar and descriptive language to make strong impact; (4) Students are able to deliver the materials. Students can use eye contacts and gestures effectively. The improvement can also be seen from their results of the post-test. The means of the scores improve from cycle to cycle. The highest score of the post test 2 is 80 and the mean score is 75. Second, the use of pairing skype can improve students motivation. Students are active and always curious to know the next materials. Moreover, the students can work individually and also in group. The speaking ability of students improve from cycle to cycle eventhough some of students are still noisy.Keywords: Speaking Ability Pairing Skype, CCM